Pengaruh Label Nomor Registrasi Barang Keamanan, Keselamatan, Kesehatan, Dan Lingkungan Hidup (K3L) Dan Harga Terhadap Keputusan Membeli Produk Seprai - Listiani, Irma (Cendekia Niaga, 2022)
The purpose of this study was to find out the influence of registration number label of Security, Safety, Health, and Environment, and also the products’ price on consumer purchase decisions on bed sheet products. This research was quantitative study with 100 respondents. The collected data were then tested for validity and reliability, then analyzed using the Structural Equation Modeling method based on PLS version 3.0. The result of data analysis show that registration number label of Security, Safety, Health, and Environment and price has a positive and significant effect on consumer purchase decisions.